Secondary postpartum hemorrhage on day 58 of cesarean section due to uterine scar rupture - Gavit, Yogita B.; Sharma, Deepika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Secondary postpartum hemorrhage is rare and affect 0.23-3% of all pregnancies. It happens between 24 hours to 12 weeks of post-delivery. These postpartum hemorrhages occur more often during normal vaginal delivery only a small subset of postpartum hemorrhages occurs after cesarean section. Delayed postpartum hemorrhage is obstetrics emergencies that occurs following vaginal or cesarean delivery, in later condition may be caused by dehiscence of uterus incision after cesarean section which can lead to severe and fatal bleeding. We herein report a case of secondary postpartum hemorrhage after cesarean section.